Peran Peghulu Dalam Penyelesaian Perkara Perceraian (Studi Kasus Pada KUA Kabupaten Aceh Barat dan Kabupaten Nagan Raya): Studi Kasus Pada KUA Kabupaten Aceh Barat dan Kabupaten Nagan Raya - Amrizal Hamsa; T Mairizal (Al Ahkam, 2021)
This article aims to analyze the role of the wedding officiant in resolving divorce cases in West Aceh and Nagan Raya districts. The wedding officiant is part of the one who resolves divorce cases in society. The wedding officiant plays a very important role in providing guidance and direction as well as forming a harmonious family by providing counseling, training and making periodic socialization programs or activities to the society to reduce the rate of divorce. The results of this study indicate that the role of the the wedding officiant is very important in an effort to provide guidance and solutions for the family who want to divorce. The wedding officiant went straight down to the community to minimize divorce numbers by providing guidance and a way out of family problems.